The Impact of Third-Party Information on Trust: Valence, Source, and Reliability. - Christiane Bozoyan; Sonja Vogt (PLoS ONE, 2016)
Economic exchange between strangers happens extremely frequently due to the growing number of internet transactions. In trust situations like online transactions, a trustor usually does not know whether she encounters a trustworthy trustee. However, the trustor might form beliefs about the trustee's trustworthiness by relying on third-party information. Different kinds of third-party information can vary dramatically in their importance to the trustor. We ran a factorial design to study how the different characteristics of third-party information affect the trustor's decision to trust. We systematically varied unregulated third-party information regarding the source (friend or a stranger), the reliability (gossip or experiences), and the valence (positive or negative) of the information. The results show that negative information is more salient for withholding trust than positive information is for placing trust. If third-party information is positive, experience of a friend has the strongest effect on trusting followed by friend's gossip. Positive information from a stranger does not matter to the trustor. With respect to negative information, the data show that even the slightest hint of an untrustworthy trustee leads to significantly less placed trust irrespective of the source or the reliability of the information.